Transgender beauty. Soggettività, genere e corpo nell’esperienza trans a Napoli - Mauriello, Marzia (Antropologia Pubblica, 2024)
This essay recounts my research among the transgender mtf (male to female) community in Naples with particular reference to my experience as a judge in some beauty contests for trans women. The knowledge/powers that have created and regulated the trans phenomenon have in recent years made their path, from the Constitutional Court ruling (n. 221/2015) to medical-psychiatric terminology (DSM V, 2013; ICD-11, 2018). Despite these changes in the direction of a greater acquisition of rights for transgender people, the process of self-recognition for the trans women I have met at the beauty contests appears closely tied to the construction of not only a compliant, “normative” body, but a beautiful one, often idealized in terms of an aesthetic chimera that leads to what Michael Taussig defines «cosmic surgery» (2012), creating what I might call “hyper-body”. In this sense, beauty contests for trans women are the litmus test for exploring how and how much a certain bodily and aesthetic ideal (that often turns into a hypertrophic but also transgressive feminine) is perceived as the only tool for self-recognition, self-realization, and social acceptance.